Image of the stars. The Epinomis and the central images of the Republic (2021)
A reading of the Epinomis dialogue is proposed within the context of the three central images of the Republic: the sun, the line and the cave. To do this, we start from the methodological assumption of the authenticity of the dialogue. A schematic summary of its main themes is then provided, according to which the three images of the Republic are explained. On these assumptions, the central thesis is argued: as a dialogue, the Epinomis is situated thematically, methodologically and interpretatively in the mathematical section of the line. In the conclusion it is argued that in this text the dialectic operates as an indication to the first intelligible realm.A reading of the Epinomis dialogue is proposed within the context of the three central images of the Republic: the sun, the line and the cave. To do this, we start from the methodological assumption of the authenticity of the dialogue. A schematic summary of its main themes is then provided, according to which the three images of the Republic are explained. On these assumptions, the central thesis is argued: as a dialogue, the Epinomis is situated thematically, methodologically and interpretatively in the mathematical section of the line. In the conclusion it is argued that in this text the dialectic operates as an indication to the first intelligible realm.